Inwentarz kościoła parafialnego w Kosowie z 1770 roku - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2021)
The presented visitation of the church of Kosów conducted at the end of the 18th century gives us the information about the administration, pastoral ministry and the emoluments of the parish church in Kosów located in the Eastern Borderlands in the Old Polish Period. It also reveals signifi cant fi gures of political and social life of the time. Its most valuable part contains data referring to the visited parish dedicated to the Holy Trinity and the Holy Cross in Kosów (Poleski) collected by Rev. Jan Nepomucen Kadłubowski; the information ranges from the smallest details or objects to religious buildings (with their equipment and vestments used for worship), residential buildings and outbuildings. The visitation also shows concern for the moral state, material goods of the parish and the order of the liturgy celebrated in the parish church in Kosów.